Efektivitas Sari Kurma terhadap Peningkatan Pertumbuhan Baduta Stunting - Ika Apriyanti; Nay Lufar; Nayya Aqnia Rahma (Faletehan Health Journal, 2024)
In 2021, Cilegon City was in the category of yellow stunting zones with a prevalence of 20.6%. This stunting prevalence rate showed that children aged 6 months to 2 years did not get adequate feeding practices and appropriate complementary foods. One way to increase the nutritional intake of babies in the first 1000 days of life is to use functional foods, such as dates. The aim of this study was to evaluate date palm juice as an adjunct for growth correction in stunted children in Cilegon City. The date juice group was the group used in the pre-experimental pre-test-post test design. The data analysis used was the dependent T-test (paired sample). The samples were 10 babies under two years old who were diagnosed stunting, selected by a total sampling technique. The results of the study showed that there was a difference in body length increase (p=0.001) and weight gain (p=0.000) after being given date palm juice. This shows that date palm juice can correct growth in babies under with stunting. The parents need to be informed and educated about the nutritional values and consumption of date juice to improve the nutritional status of their babies.